Teacher attunement to peer‐nominated aggressors. Issue 3 (25th October 2016) - Dawes, Molly; Chen, Chin‐Chih; Zumbrunn, Sharon K.; Mehtaji, Meera; Farmer, Thomas W.; Hamm, Jill V.
Abstract : This study examined the associations between teacher attunement to aggressive students and students' characteristics in a sample ( n = 278) of youth in 5th‐grade classrooms with the assumption that certain student characteristics may either prime or hinder teachers' attunement to aggressive students. Teacher attunement was measured as the agreement between teacher‐ and peer‐nominations for students who start fights . Teachers rated their students on the following characteristics: academic competence, affiliation, popularity, internalizing behavior, and Olympian qualities. Higher affiliation, popularity, and internalizing behavior were associated with decreased odds for teacher attunement to aggressive youth. Higher Olympian qualities were associated with increased odds for teacher attunement to aggressive youth. Implications for interventions are discussed. Aggr. Behav. 43:263–272, 2017. © 2016 Wiley Periodicals, Inc.